Health measurement profile of older adults in Sleman District, Yogyakarta: its correlation with low-grade chronic inflammation in hypertension - Adyarini, Dwita Dyah; Rohmah, Siti Nur Rohmah; Sattwika, Prenali Dwisthi; Handayaningsih, Anastasia Evi; Probosuseno, Probosuseno; Sinorita, Hemi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
The older adult often experiences a low-grade chronic inflammation that commonly manifests in various conditions without infection, including hypertension. The serum neutrophil-to-lymphocyte ratio (NLR) and hyperuricemia are important markers for various diseases including hypertension. Older adult accounts for 17.33% of the total population of Yogyakarta Special Province, which is the highest compared to other provinces. The study aimed to evaluate the relationship between NLR and hyperuricemia with hypertension among adult patients in Sleman District, Yogyakarta, Indonesia. It was a community-based cross-sectional nested study involving 90 older adults aged ≥70 y.o. living around of the Sleman Health and Demographic Surveillance System (HDSS). Data of demographic and health characteristics of the subjects were collected. Independent t test, and Mann Whitney test were used to analyze mean differences between normotensive and hypertensive groups.  Multivariate analysis with logistic regression was used to analyze correlation between all variables. The results showed 59 respondents (65%) suffered from hypertension and 31 (35%) respondents had normal and pre-hypertension. No significantly different in almost of the subject characteristics between the normotensive and the hypertensive groups was observed (p>0.05). However, significantly different between the normotensive group and the hypertensive group was observed in the history of hypertension, blood pressure/BP, mean arterial pressure/MAP, abdominal circumstance/AC, fasting blood glucose/FBG, triglyceride, and hemoglobin (p<0.05). No significantly different in the NLR and HsCRP levels of the normotensive group compared to the hypertensive groups were observed (p>0.05). However, the uric acid level of the hypertensive group [5.6 (2.9-9.4 mg/dL)] was significantly higher than that the normotensive group [4.7 (2.9-8.0 mg/dL)] (p=0.042), although it was no significantly relationship with hypertension (p>0.05). In conclusion, there is no relationship between NLR, HsCRP and uric acid with hypertension among middle old and oldest old in Sleman District.